2014
DOI: 10.1007/s11739-014-1163-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of venous thromboembolism in patients with liver diseases: a systematic review and meta-analysis

Abstract: The risk of venous thromboembolism (VTE) may be increased in patients with liver diseases. A systematic review and meta-analysis were conducted to analyze the epidemiology of VTE in such patients. All relevant studies were searched via the PubMed, EMBASE, and Cochrane Library databases. The incidence and prevalence of VTE were pooled using random-effect models. Subgroup analyses were conducted according to the type of VTE [deep vein thrombosis (DVT), pulmonary embolism (PE)], type of liver disease (liver cirrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 42 publications
5
37
1
Order By: Relevance
“…The pooled proportion is unaffected by diagnosis (liver cirrhosis or unclassified liver diseases), whereas studies involving fewer than 1000 patients show a slightly higher incidence and prevalence compared to those involving more than 1000 patients, likely due to an enhanced possibility of selection bias [17]. Additional data analyzed by Qi et al [17] present evidence that in the majority of studies, the risk of VTE is increased in CLD patients by approximately 1.7-to 2-fold with respect to the controls, as previously reported [8]. The 1.7-fold increase in risk of VTE in cirrhotic patients has been recently confirmed in a nationwide study [18].…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…The pooled proportion is unaffected by diagnosis (liver cirrhosis or unclassified liver diseases), whereas studies involving fewer than 1000 patients show a slightly higher incidence and prevalence compared to those involving more than 1000 patients, likely due to an enhanced possibility of selection bias [17]. Additional data analyzed by Qi et al [17] present evidence that in the majority of studies, the risk of VTE is increased in CLD patients by approximately 1.7-to 2-fold with respect to the controls, as previously reported [8]. The 1.7-fold increase in risk of VTE in cirrhotic patients has been recently confirmed in a nationwide study [18].…”
mentioning
confidence: 91%
“…Qi et al [17] acknowledge the limitations of their study, including the significant heterogeneity found in nearly all meta-analyses. However, they confirm that a non-trivial proportion of CLD patients are prone to an increased thrombotic risk; this calls for studies aimed at the investigation of the risk stratification of patients according to the presence of patient-or disease-linked factors, and the opportunity of thromboprophylaxis in this setting.…”
mentioning
confidence: 96%
See 3 more Smart Citations